Enhancing Supercapacitor Performance with Cassava Tuber- Bamboo Stem Blended Porous Activated Carbon: An Environmentally Friendly Approach - Muthi Aturroifah Nuviya Illa; Diantoro Markus; Meevasana Worawat; Maensiri Santi (E3S Web of Conferences, 2024)
Supercapacitor electrodes based on porous activated carbon from a blend of cassava tubers and bamboo stems were successfully synthesized using a chemical activation method with a 4M KOH activator. In this study, we characterized the morphological structure of porous activated carbon blended from cassava tubers and bamboo stems using SEM, while the electrochemical performance was tested using GCD, CV, and EIS. The porous activated carbon blend derived from cassava tubers and bamboo stems exhibits a micro-meso pore morphology, resulting in superior electrolyte ion storage capacity when compared to the carbon precursors of cassava tubers and bamboo stems. The porous activated carbon blend from cassava tubers and bamboo stems, serving as a supercapacitor electrode, demonstrates specific capacitance, energy density, and power density values of 43.44 F/g, 4.81 Wh/kg, and 178.64 W/kg, respectively. The CV curve results show that the supercapacitor electrode has EDLC properties, with Rs and Rct of 15.52 Ω and 7.40 Ω. The results of the research provide a valuable contribution to the development of efficient and sustainable electrochemical materials, with potential broad applications in energy storage technologies.